2002
DOI: 10.1176/appi.ajp.159.12.2042
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficiency of Borderline Personality Disorder Criteria in Hospitalized Adolescents: Comparison With Hospitalized Adults

Abstract: In hospitalized patients, borderline personality disorder and its symptoms appear to be as frequent for adolescents as for adults. Despite these surface similarities between groups with respect to symptom patterns, several differences were found at the level of the diagnostic efficiency for individual borderline personality disorder criteria. These differences may shed light on the nature of borderline psychopathology during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 28 publications
10
57
0
8
Order By: Relevance
“…In addition, items demonstrated good discrimination and difficulty parameters. The most difficult items included abandonment fears and suicidal behavior; this finding converges with research in adults that has demonstrated that abandonment fears are the least commonly exhibited BPD symptom (22,28) and that suicidal behaviors are uncommon among young children (29). With regard to measurement equivalence across gender, although five criteria demonstrated differential item functioning, this balanced out at the level of the total set of the nine DSM-IV BPD criteria, which suggests that the use of the full nine criteria is psychometrically valid and advisable.…”
Section: Categorical Diagnosissupporting
confidence: 81%
“…In addition, items demonstrated good discrimination and difficulty parameters. The most difficult items included abandonment fears and suicidal behavior; this finding converges with research in adults that has demonstrated that abandonment fears are the least commonly exhibited BPD symptom (22,28) and that suicidal behaviors are uncommon among young children (29). With regard to measurement equivalence across gender, although five criteria demonstrated differential item functioning, this balanced out at the level of the total set of the nine DSM-IV BPD criteria, which suggests that the use of the full nine criteria is psychometrically valid and advisable.…”
Section: Categorical Diagnosissupporting
confidence: 81%
“…Second, the study focused on lifetime self-harm rather than self-harm within the prison because our interest was in the stable personality traits of this sample (which are likely to have been present prior to incarceration as they develop in early adolescence/early adulthood e.g., Becker, Grilo, Edell & McGlashan, 2002), that might explain the endorsement of specific functions. As a result, generalisation of the findings to a specific observation period (e.g., 1-month prevalence, or past 12 months) either in our outside of the prison is not possible, and it means that we cannot be sure whether some self-harm occurred prior to criminal activity.…”
Section: Running Head: Reasons For Non-suicidal Self-harm In Adult Mamentioning
confidence: 99%
“…Le dĂ©part des personnes significatives, mĂȘme momentanĂ©, apparaĂźt alors particuliĂšrement menaçant puisque sans l'autre, il y a une perte des ancrages internes (Westen et al, 2011). La peur de l'abandon est un Ă©lĂ©ment fondamental de la psychopathologie limite (Goldman, D'Angelo, DeMaso et o 3 Mezzacappa, 1992) qui a d'ailleurs Ă©tĂ© identifiĂ© comme le symptĂŽme ayant la plus grande validitĂ© prĂ©dictive d'un diagnostic de TPL chez les adolescents (Becker, Grilo, Edell et McGlashan, 2002).…”
Section: Discussionunclassified